The Perspective of Thammislam Foundation School Thailand Students on the Teaching of Non-Native Speaker Teachers - Hasanah, Nurul; Harisma, Rita (CV. PUSDIKRA MITRA JAYA, 2023)
This study investigates students' perceptions of teachers teaching Non-Native Speakers at Thammislam Foundation School Thailand. This study uses descriptive research methods by collecting data through interviews and interviews given to class students at the school. The tables presented in this study cover various aspects of teaching Non-Native Speaker teachers, such as the using language, humor, multi-modal tools, group discussion groups, and assessment of student class participation. This study’s results indicate the most positive perceptions of Non-Native Speaker teachers. th Most students agree that Non-Native Speaker teachers provide the subject matter in a fun way and can interact with students in class. In addition, most students agree that Non-Native Speaker teachers use body language, humor, and multi-modal tools to facilitate teaching. This shows that Non-Native Speaker teachers at Thammislam Foundation School Thailand successfully created an interesting, interactive and fun learning environment for students. Furthermore, most students agree that Non-Native Speaker teachers design discussion groups and solve problems in class. These activities are considered to increase student participation and develop critical and social thinking skills. In addition, the majority of students also agreed that Non-Native Speaker teachers assess student class participation. Class participation assessments effectively encourage student engagement in learning and build a collaborative classroom environment.